Alginate nanoformulation: influence of process and selected variables - Hazem, Choukaife; Doolaanea, Abd Almonem; Alfatama, Mulham (MDPI AG, 2020)
Nanocarriers are defined as structures and devices that are constructed using nanomaterials which add functionality to the encapsulants. Being small in size and having a customized surface, improved solubility and multi-functionality, it is envisaged that nanoparticles will continue to create new biomedical applications owing to their stability, solubility, and bioavailability, as well as controlled release of drugs. The type and physiochemical as well as morphological attributes of nanoparticles influence their interaction with living cells and determine the route of administration, clearance, as well as related toxic effects. Over the past decades, biodegradable polymers such as polysaccharides have drowned a great deal of attention in pharmaceutical industry with respect to designing of drug delivery systems. On this note, biodegradable polymeric nanocarrier is deemed to control the release of the drug, stabilize labile molecules from degradation and site-specific drug targeting, with the main aim of reducing the dosing frequency and prolonging the therapeutic outcomes. Thus, it is essential to select the appropriate biopolymer material, e.g., sodium alginate to formulate nanoparticles for controlled drug delivery. Alginate has attracted considerable interest in pharmaceutical and biomedical applications as a matrix material of nanocarriers due to its inherent biological properties, including good biocompatibility and biodegradability. Various techniques have been adopted to synthesize alginate nanoparticles in order to introduce more rational, coherent, efficient and cost-effective properties. This review highlights the most used and recent manufacturing techniques of alginate-based nanoparticulate delivery system, including emulsification/gelation complexation, layer-by-layer, spray drying, electrospray and electrospinning methods. Besides, the effects of the main processing and formulation parameters on alginate nanoparticles are also summarized